IMPLICATIONS OF DEBT TO ASSET RATIO, RETURN ON EQUITY AND PRICE TO BOOK VALUE ON STOCK PRICES (Study In The Consumer Goods Industry Sector Listed On The Idx For The Period 2017 – 2021) - Tetty Lasniroha Sarumpaet; R. Ait Novatiani; Veronica Christina; Bachtiar Asikin; Robertus Ary Novianto (SEAN Institute, 2023)
This research aims to investigate the correlates Price to Book Value to Stock Prices, Return on Equity, and Debt to Asset Ratio in manufacturing firms in Indonesia's consumer products manufacturing sector. The Composite Stock Price Index (IHSG) decreased constantly for 5 (five) sequential years as a result of the phenomenon of manufacturing businesses in the consumer products industry sector. By performing out descriptive investigations, confirming in describing the status of manufacturing firms in the consumer products industry sector, and examining research factors, this kind of study aims to confirm the comparability between theoretical and empiric. The sample assessed was comprised of 25 firms listed using a purposive judgment selection technique from either the research population of 53 manufacturing companies in the consumer products industry sector listed on the Indonesia Stock Exchange in 2017–2021, according to the following criteria: In 2017–2021, manufacturing businesses in the consumer durables industry sector registered on the Indonesia Stock Exchange, undertook an IPO before 2017, published financial reports during 2017–2021, and never reported a loss. Panel regression is the analytical method employed, the t-statistic test is used for partial hypothesis testing, and the F-statistic test used for simultaneous hypothesis testing. The study's results indicate that while Price to Book Value and Return on Equity both significantly affect stock prices, the Debt to Asset Ratio has no effect on stock prices.